ISLAM DAN ILMU PENGETAHUAN - Lutfi, Magfiroh; Alik, Mustofa; Miftahul, Iqbal (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2024)
In essence, science aims to search for scientific truth in accordance with scientific principles. With science, every human being will be able to obtain the truth through certain processes, either by conducting scientific research or by various other means. Knowledge in Islam is seen as a human need to achieve prosperity in life in the world and makes it easier to know God. Therefore, Islam views that science is part of carrying out human obligations as creatures of Allah SWT. the sensible. Islam is a universal religion that has been valid throughout the ages. Islam is not only open to innovations carried out by science, but also encourages the achievement of this progress. Thus, through scientific research, humans can develop theories which are descriptions of natural phenomena